Islam and revolution/ edited by Asghar Ali Engineer - "Ali, Asghar (ed.)" (Delhi, 1984)
The book contains number of articles on countries like Iran, South Yemen, Afghanistan, Libya, Malaysia, Algeria etc.where revolution with left orientation has taken place. This book discusses the situation of Muslims in socialist countries like the Soviet Union and China.